ANALISIS TINGKAT PEMAHAMAN PENGELOLA DANA BANTUAN OPERASIONAL SEKOLAH TERHADAP PENGGUNAAN DANA DAN PELAPORAN PERTANGGUNGJAWABAN (Studi Kasus Pada Sekolah Dasar Dan Sekolah Menengah Pertama Di Kecamatan Bukit Kecil Palembang) - Lisdjuniar, Lisdjuniar; Sabrina, Nina (Universitas Muhammadiyah Palembang, 2017)
ABSTRACT This research was conducted in Bukit Kecil sub-district of Palembang. The type of this research is descriptive research. The first variable used is understanding level of BOS funds managers with indicators of understand, quite understand and not understand. The second variable is the use of funds with indicators of purchasing / duplicating textbooks, financing all activities in the context of admission of new students, financing of learning activities, financing examinations, purchasing consumables, financing of power and services subscriptions, financing school care, monthly teacher fee payment, financing teacher professional development and computer equipment purchase. The third variable is reporting with indicators of the central BOS management team reports, provincial BOS management team reports, district / city BOS management team reports and school BOS management reports. The data used are primary and secondary data. Data collection techniques are interview lists and documentation. Data analysis used is qualitative data analysis, quantitative and data analysis techniques. The results show that the fund managers of School Operational Fund (BOS) have already understood in using BOS funds in accordance with the provisions that have been determined.